2010
DOI: 10.4103/0253-7613.71894
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic misadventure with paracetamol in children

Abstract: Paracetamol (acetaminophen), though considered a safe, “over the counter” analgesic and antipyretic, can cause liver injury with overdose. Therapeutic misadventure is a unique problem where the existing nomogram used for acute poisoning is not applicable. In this context, early initiation of N-acetylcysteine even before a biochemical evidence of liver injury may be beneficial. A series of 6 children with this type of paracetamol overdose are presented here to increase the awareness and understanding of this pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 10 publications
0
8
0
1
Order By: Relevance
“…However, there are few reports on the toxicity of acetaminophen in India is available. 6) Therefore the present study was designed to evaluate the sub-acute toxicity of acetaminophen in order to find out no observed effect level, target organ toxicity and reversibility of signs of toxicity after the recovery period in Sprague Dawley (SD) rats.…”
mentioning
confidence: 99%
“…However, there are few reports on the toxicity of acetaminophen in India is available. 6) Therefore the present study was designed to evaluate the sub-acute toxicity of acetaminophen in order to find out no observed effect level, target organ toxicity and reversibility of signs of toxicity after the recovery period in Sprague Dawley (SD) rats.…”
mentioning
confidence: 99%
“…Es por esto que el uso de los antipiréticos deberá estar sustentado en un uso racional, pues no se trata de un medicamento inocuo. Por el contrario, existen múltiples evidencias que cuestionan el uso rutinario de antipiréticos, sustentadas en el riesgo al que se someten los niños debido a su toxicidad (45)(46)(47). Sin embargo, se deben considerar los niños que no toleran el aumento de las demandas metabólicas y los que poseen condiciones específicas de base, como la presencia de enfermedades crónicas o graves, en las que el manejo deberá ser diferencial y enfocado en lograr la normotermia, ya que en ellos las reservas metabólicas se encuentran disminuidas, por tanto se debe mejorar el reconocimiento, la evaluación y el manejo de la fiebre en lo que respecta a enfermedades subyacentes en los niños (48).…”
Section: El Uso De Antipiréticos: Una Rutina En Contravía De La Saludunclassified
“…3 ), which is 10–15 times the recommended dosage [ 78 ], even though idiosyncratic reactions associated to increased activity of the hepatic cytochrome P450 detoxifying system have been reported [ 85 ]. Sustained dosing (>1 day) with >90 mg/kg/day (whereas the recommended dosing 60 mg/kg/day) puts children aged <2 years at high risk for hepatotoxicity [ 81 ]. Case reports describe children presenting with paracetamol toxicity after sustained dosing of 100–367 mg/kg/day [ 81 ].…”
Section: Tolerability and Safetymentioning
confidence: 99%
“…Sustained dosing (>1 day) with >90 mg/kg/day (whereas the recommended dosing 60 mg/kg/day) puts children aged <2 years at high risk for hepatotoxicity [ 81 ]. Case reports describe children presenting with paracetamol toxicity after sustained dosing of 100–367 mg/kg/day [ 81 ]. A recent study conducted in Australia and New Zealand revealed that hepatic failure due to paracetamol ingestion occurred in children mostly as a result of medication errors such as doses in excess of 120 mg/kg/day, double dose, too frequent administration, coadministration of other medicines containing paracetamol or regular paracetamol for up to 24 days [ 82 ].…”
Section: Tolerability and Safetymentioning
confidence: 99%